1998
DOI: 10.1007/s007050050332
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Epstein-Barr virus infection in the epithelial cells and lymphocytes of non-neoplastic tonsils by in situ hybridization and in situ PCR

Abstract: Non-neoplastic tonsils were analyzed for detection of Epstein-Barr virus (EBV)-positive cells by in situ hybridization and in situ PCR. EBV-encoded small nuclear RNA 1(EBER1)-positive cells were found in 28.2% of the tonsils and were evenly localized in the extrafollicular area and within germinal centers. Latent membrane protein 1 (LMP1)-positive cells were also dispersed in the extrafollicular and germinal center. Using in situ DNA-DNA hybridization, the EBV-positive signals were observed in the upper epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 24 publications
5
26
1
Order By: Relevance
“…From there, the virus may reach the endothelial cells locally or via circulating hematopoietic cells and contribute to the formation of the vascular lesions typical of KS. This hypothesis is in line with the infection modalities of the closest related known human herpesvirus, EBV, which is associated with lymphoid and epithelial lesions (25,26,28). EBV infects epithelial cells in vivo (49,52,56), transforms epithelial cells, and inhibits cell differentiation (48).…”
Section: Discussionsupporting
confidence: 57%
“…From there, the virus may reach the endothelial cells locally or via circulating hematopoietic cells and contribute to the formation of the vascular lesions typical of KS. This hypothesis is in line with the infection modalities of the closest related known human herpesvirus, EBV, which is associated with lymphoid and epithelial lesions (25,26,28). EBV infects epithelial cells in vivo (49,52,56), transforms epithelial cells, and inhibits cell differentiation (48).…”
Section: Discussionsupporting
confidence: 57%
“…Some studies have reported the presence of EBV DNA in desquamated squamous epithelial cells and in tonsil epithelium. [25][26][27] In contrast, other studies have reported no virus in desquamated epithelial cells or unequivocal evidence of EBV-infected tonsillar epithelial cells by EBER ISH and/or LMP1 immunostaining. 4,14,28 The present results, based upon exhaustive histopathologic evaluation of many tonsil sections, provide direct in situ evidence that normal epithelial cells in tonsillar crypts from immunocompetent hosts may rarely be infected by EBV.…”
Section: Ebv In Tonsils Sd Hudnall Et Almentioning
confidence: 89%
“…Many researchers have suggested that the tonsils are a possible replication site for this virus. 2,3,8,13 Molecular techniques have been used often for diagnosing and monitoring patients with virus diseases. The EBV-DNA can be identified by in situ hybridization (ISH) and the polymerase chain reaction (PCR); some authors consider both equally sensitive for detecting the EBV.…”
Section: Discussionmentioning
confidence: 99%